Analisis Proses Quality Control di Area Packing Menggunakan Metode Dmaic di PT. XYZ - Panjaitan, Wynda Gerika Br; Suntoro, Suntoro; Puspitaningrum , Ita (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2026)
The packing process is a critical stage in logistics operations, especially for Third Party Logistics (3PL) companies serving the automotive sector. Delivery accuracy determines customer satisfaction and compliance with the Service Level Agreement (SLA). At PT. XYZ, various types of defects are still found in the packing area, such as label defects, mixed goods, and document discrepancies. This study aims to analyze the quality control process in the packing area using the DMAIC (Define, Measure, Analyze, Improve, Control) method. The research approach uses a quantitative descriptive method with data collection through observation, interviews, and documentation during the period of June-December 2025, covering 48,800 shipping units with 902 defective units. Data analysis was performed using Pareto Charts, Fishbone Diagrams (4M+1E), P-Charts, and Defect Per Million Opportunity (DPMO) calculations. The results show that label defects (222 cases) and mixed goods (158 cases) are the most dominant. P-Chart analysis reveals that the process is not statistically stable due to special cause variations in July and August exceeding the Upper Control Limit (UCL). Overall, the process achieved DPMO = 4,586 (sigma level 4.1) and DPU = 1.83%. Although better than the Indonesian logistics industry standard (3σ), this process is not yet adequate for global automotive customer standards. Proposed improvements include implementing a double-check system, One-Order-One-Station principle, visual marking, and document verification before packing.